STUDI NORMATIF YURIDIS SENGKETA PENYALAH GUNAAN HARTA GONO GINI - Ubaidillah, M. Burhanuddin; Shinwanuddin, M. (USRATUNA: Jurnal Hukum Keluarga Islam, 2023)
In practice, disputes often arise between married couples in the division of marital property in court. Even in the court process, there are often disputes about the division of marital property, which further complicates the divorce process because each party claims that the property is part of their rights. This article focuses on a normative juridical study of disputes over the misuse of marital property due to death, divorce, and polygamy. It begins by examining the concept of normative juridical methods, the historical roots of the term "marital property," the legal basis of marital property in Indonesian law, and a normative juridical study of disputes over the misuse of marital property due to death, divorce, and polygamy. The research results show that husbands and wives have the same rights and obligations to marital property. Wives have the same rights and obligations to marital property, namely to maintain their husband's property that is in their possession and joint property. The use of marital property by the husband for the needs of children from the first marriage must be with the wife's consent. A husband who does not fulfill his obligations, such as not providing for his wife, is included in the category of nusyuz and neglects his obligation to ask for permission to use marital property with his second wife. The solution that can be taken is consultation and peace. If the peace effort fails and even triggers a dispute (syiqaq) between the husband and wife, the solution is to bring in a mediator (hakam) from each party.